Social in the improvement of the political culture of society partnership model (Global Scientific Review, 2024)
Social partnership serves to balance the interests of society, to harmonize the interests of state and non-state organizations. In particular, it plays an important role in applying the socio-political relations of citizens between the state and non-governmental organizations to the social life of the society based on democratic principles. In Uzbekistan, the best practices of developed foreign countries are being thoroughly studied in the application of social partnership relations to sociopolitical life. The model of social partnership in Uzbekistan is aimed at ensuring the rights and interests and freedoms of all levels of social life. Also, the current model of social partnership, the advanced methods of models of foreign countries that have reached the stage of development are studied on a scientific and creative basis. However, in our country, the existing social partnership is being implemented in a way that is specific to Uzbekistan and is based on the needs and requirements.